PERAN RUPBASAN (RUMAH PENYIMPANAN BENDA SITAAN NEGARA) DALAM PENEGAKAN HUKUM - Sigit Setyadi (Kajian Hukum, 2016)
AbstractConfiscated objects are obtained due to criminal cases, has given rise to a complicated problem because in addition to its importance as evidence in court proceedings, as well as its value is very precious, good value for the case, as well as the nominal value, especially in a big case like corruption. For that research in Yogyakarta, especially in Bantul, the problem "the Role of Home for State Confisticated Obeject Storage (RUPBASAN) in Law Enforcement. This type of research is yuridicalapplied.From the research conducted, it can be concluded as follows: 1.RUPBASAN in law enforcement, quite a role, particularly for the legal certainty of goods into evidence a criminal case. To ensure the arrangement is enough to legislation, government regulations, the Minister / Director General of the force, which can be applied in the field, namely Law No. 8 Year1981 on Criminal Proceedings, which is known as the Criminal Procedure Code, Law No. 12 Year 1995 on Corrections; RUPBASAN specific provision contained in Article 44-46 Criminal Procedure Code, and PP 27 Year 1983 on the Implementation of the Book of the Law of Criminal Law; Regulation of Minister of Law and Human Rights No. M.HH-05.OT.01.01 Year 2010 on Organization and Administration of the Ministry of JLaw and Human Rights of the Republic of Indonesia; Regulation of Minister of Law and Human Rights No. 16 Year 2014 on Procedures for Management of State Confiscated Objects; Decision of the Director General PasNumber: PAS-140.PK.02.01 Year 2015 on Implementation Guidelines for Management of Confiscated Objects of State and the House of State Confiscated Objects Storage.With the implementation of the provisions of proficiency level, in RUPBASAN will be secured, the existance of legal certainty, so that especially the people who lodged a criminal case no longer be worried about the goods, especially for goods in execution are not deprived of the state as evidence of criminal case.2. Concerning to the constraints faced RUPBASAN in law enforcement: a.Concerning to the infrastructure are on average not sufficient for the execution of tasks in the field, particularly equipment that is very expensive; b. Difficulties associated with particular expertise in the certain field, especially research Bashan, required specialized personnel (experts) can not always be met by the officer in RUPBASAN; c. Adequate security force is necessary, in order to keep the state confiscated goods that have a very important role in the judicial process.3. Solutions to address these constraints: a. to use equipment available to carry out their duties even with equipment that was not optimal; b. to overcome the lack of experts in specific fields related to research, often conducted (MoU) with various agencies to address them. Keywords: role, RUPBASAN, law enforcement.